Direct external imaging of nascent cancer, tumor progression, angiogenesis, and metastasis on internal organs in the fluorescent orthotopic model - Yang, Meng (The National Academy of Sciences, 2002)
Mouse tumor models have undergone profound improvements in the fidelity of emulating human disease. Replacing ectopic s.c. implantation with organ-specific orthotopic implantation reproduces human tumor growth and metastasis. Strong fluorescent labeling with green fluorescent protein along with inexpensive video detectors, positioned externally to the mouse, allows the monitoring of details of tumor growth, angiogenesis, and metastatic spread. However, the sensitivity of external imaging is limited by light scattering in intervening tissue, most especially in skin. Opening a reversible skin-flap in the light path markedly reduces signal attenuation, increasing detection sensitivity many-fold. The observable depth of tissue is thereby greatly increased and many tumors that were previously hidden are now clearly observable. This report presents tumor images and related quantitative growth data previously impossible to obtain. Single tumor cells, expressing green fluorescent protein, were seeded on the brain image through a scalp skin-flap. Lung tumor microfoci representing a few cells are viewed through a skin-flap over the chest wall, while contralateral micrometastases were imaged through the corresponding skin-flap. Pancreatic tumors and their angiogenic microvessels were imaged by means of a peritoneal wall skin-flap. A skin-flap over the liver allowed imaging of physiologically relevant micrometastases originating in an orthotopically implanted tumor. Single tumor cells on the liver arising from intraportal injection also were detectable. Possible future technical developments are suggested by the image, through a lower-abdominal skin-flap, of an invasive prostate tumor expressing both red and green fluorescent proteins in separate colonies.